Entrepreneurship, Skills for Santri to Become Job Creators - Titien Agustina; Dodik Jatmika; Sampurnawati Sampurnawati; Wenny Djuarni (Lafadz Jaya Publisher, 2023)
This study aims to determine fine practices in entrepreneurship for santri (Islamic boarding school students) based on personal characteristic factors (self-efficacy, locus of control, need for achievement, and adversity quotient) that exist in every human being. The research object is santri of the Manbaul Ulum Islamic Boarding School, South Kalimantan, which are generally limited in terms of curriculum content that equips them with productive skills as provisions of practices in society, becoming leaders in society, as well as role models in good economic and social religious activities. The progress of a nation is mainly determined by the advancement of entrepreneurship which is marked by the presence of a high entrepreneurial spirit of individuals so that they have rich initiative and develop creativity and innovation in seeing opportunities and opportunities around them. The Islamic boarding school curriculum generally contains religious education. Educational content that provides life skills in the economic field is very limited and even very limited. In reality, when they finish their education at Islamic boarding schools, students will face highly powerful economic activities that can even create jobs for the people around them. Through a quantitative descriptive research method on 71 students in Class XI and XII with multiple linear regression analysis, the results show that self-efficacy, locus of control, need for achievement, and adversity quotient partially have a significant effect on students’ entrepreneurial intentions. The most dominant influence in student entrepreneurship is the adversity quotient